Pengembangan Model Pembelajaran POTS (Preconditioning, Organizing, Thinking, Simulating) untuk Pembelajaran Fisika Kuantum - Zainur Rasyid Ridlo; Indrawati Indrawati; Agus Abdul Gani (Jurnal Pembelajaran dan Pendidikan Sains, 2016)
Quantum physics is one of the subjects on advanced physics. Characters of quantum physics is abstract and uses complex mathematical equations. The difficulties experienced by students in study of quantum physics related by character quantum physics and mathematical equations. Required learning model that is capable of quantum physics makes learning more effective and efficient. Learning model that was developed and implemented in the course of quantum physics is a POTS learning model that consists of four stages: preconditioning, organizing, thinking , and simulating. Development of model POTS using design 4 D (define, design, develop, desseminate). The results of the development model POTS is valid. Implementation of model POTS shows the average value of the effectiveness of the learning outcome indicators reached either category (76.85). Students' learning activities using POTS models reaching the active category (74.02 %).